2020
DOI: 10.7717/peerj.9925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taphonomic deformation on geometric morphometric analysis of fossils: a study using the dicynodontDiictodon feliceps(Therapsida, Anomodontia)

Abstract: Taphonomic deformation, the distortion of fossils as a result of geological processes, poses problems for the use of geometric morphometrics in addressing paleobiological questions. Signal from biological variation, such as ontogenetic trends and sexual dimorphism, may be lost if variation from deformation is too high. Here, we investigate the effects of taphonomic deformation on geometric morphometric analyses of the abundant, well known Permian therapsid Diictodon feliceps. Distorted Diictodon crania can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…In common with previous studies, size was found to be strongly correlated with whole-skull shape in P. andrewsi [ 13 , 32 , 33 ], accounting for around 52% of total shape variation in this dataset and reflecting drastic changes in skull shape during ontogeny [ 28 ]. Although all modules showed some degree of change, the parietal-squamosal frill consistently displayed the highest rates of size and shape change through ontogeny, as well as the highest morphological variance independent of size, expanding significantly during ontogeny to form a large, conspicuous structure ( figure 3 a,b ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In common with previous studies, size was found to be strongly correlated with whole-skull shape in P. andrewsi [ 13 , 32 , 33 ], accounting for around 52% of total shape variation in this dataset and reflecting drastic changes in skull shape during ontogeny [ 28 ]. Although all modules showed some degree of change, the parietal-squamosal frill consistently displayed the highest rates of size and shape change through ontogeny, as well as the highest morphological variance independent of size, expanding significantly during ontogeny to form a large, conspicuous structure ( figure 3 a,b ).…”
Section: Discussionsupporting
confidence: 88%
“…PC4 (4.9% of total shape variation) shows obvious signs of taphonomic deformation, i.e. flattening of the skull and deformation of the orbit [ 32 ] (electronic supplementary material, figure S6). Although arguably not as clear in PCs 2 and 3, it is likely that effects of taphonomic deformation are distributed more subtly among these and subsequent PC axes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we demonstrate this condition by examining exclusively belinurid species: the constructed morphospace is polarized by species with genal spines (e.g., Euproops and Belinurus ) and those lacking the morphology (e.g., Prolimulus , Alanops ). Although morphospace is impacted by taphonomic modification of fossils ( Kammerer et al, 2020 ), this is not apparent within the first two PCs ( Bicknell et al, 2019b ). Furthermore, as the cuticular xiphosurid exoskeleton requires exceptional preservation conditions, these fossils are seldom subject to the tectonic strain observed in trilobites ( Cooper, 1990 ; Hughes & Jell, 1992 ).…”
Section: Discussionmentioning
confidence: 99%